Abstracts - Espinoza M., A.; Robles y Zarate, J.; Saltazar F., E.; Roa J., C.; Gutierrez Mazzotti, C.; Fernandez Mas, R.; Van der Malden, C.; Servin, G.; Rebolledo, H. (Revista Mexicana de Ingenieria Biomedica, 1988)
Summaries of: -Bone fixation by axial traction by screw for the treatment of fractures, diaphysectomies and pseudoarthrosis. -Electromyometrium compatible with a PC. -Calculation of the median frequency of the EMG spectrum during the occurrence of postoperative tremor. -Spatial mapping system of the electroencephalogram spectral components. -System for neonatal monitoring of cardiac and respiratory frequencies, as well as body temperature.